2008
DOI: 10.1021/ol7029678
|View full text |Cite
|
Sign up to set email alerts
|

Electronegative Oligothiophenes Based on Difluorodioxocyclopentene-Annelated Thiophenes:  Synthesis, Properties, and n-Type FET Performances

Abstract: A series of oligothiophenes containing difluorodioxocyclopentene-annelated thiophene units was synthesized, and their electronic properties and structures were investigated by spectroscopic and electrochemical measurements and X-ray analyses. The oligothiophenes having the terminal difluorodioxocyclopentene annelations showed n-type semiconducting behavior on FET devices, and the quaterthiophene revealed field-effect electron mobility as high as 1.3 x 10(-2) cm2 V(-1) s(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 18 publications
0
54
0
Order By: Relevance
“…It can also be found that the IP value increases when the HOMO energy level decreases, whereas the absolute value of EA increases when the LUMO energy level decreases. Because LUMO energy level decreases can make the charge carrier more stable and electron affinity increases can reduce the sensitivity of mobile electrons, 97,98 it is indicated that DADK should be more favor to function as n-type organic semiconductor than DADF. Figure 2 shows the simulated absorption spectra of DADF and DADK in tetrahydrofuran (THF) solution with PCM model.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It can also be found that the IP value increases when the HOMO energy level decreases, whereas the absolute value of EA increases when the LUMO energy level decreases. Because LUMO energy level decreases can make the charge carrier more stable and electron affinity increases can reduce the sensitivity of mobile electrons, 97,98 it is indicated that DADK should be more favor to function as n-type organic semiconductor than DADF. Figure 2 shows the simulated absorption spectra of DADF and DADK in tetrahydrofuran (THF) solution with PCM model.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A molecule with high electronegativity might be more efficient as an electron transport material because it can pull more electrons towards itself, resulting in high electron charge transfer. 57,[71][72][73]94 The trend of electronegativities in compound 1 > compound 2 revealed that the former might be better as an electron transport material as compared with the latter. The reorganization Table 3 The vertical/adiabatic ionization potential and electron affinity, hole extraction potential, electron extraction potential, electronegativity and reorganization energy for hole a l h /electron l e at the B3LYP/6-31G** level of theory.…”
Section: Charge Transfer Propertiesmentioning
confidence: 99%
“…Subsequently, we have systematically designed and synthesized a series of electron-deficient thiophene units annelated with a ring that contains the electronwithdrawing functional groups. [16][17][18][19] For example, the LUMO energy level of terthiophene BCB comprised of difluorodioxocyclopenta- [b] thiophene (B) and -[c]thiophene (C) units was estimated to be − 4.17 eV; this value is low enough to exhibit an n-type semiconducting nature in OFETs. 16 To improve the solubility in organic solvents, we synthesized quinquethiophene BHCHB, which consists of the difluorodioxocyclopentene-annelated thiophene and 3-hexylthiophene (H).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] For example, the LUMO energy level of terthiophene BCB comprised of difluorodioxocyclopenta- [b] thiophene (B) and -[c]thiophene (C) units was estimated to be − 4.17 eV; this value is low enough to exhibit an n-type semiconducting nature in OFETs. 16 To improve the solubility in organic solvents, we synthesized quinquethiophene BHCHB, which consists of the difluorodioxocyclopentene-annelated thiophene and 3-hexylthiophene (H). 17 Although the introduction of electron-donating H units elevated the LUMO energy level to − 3.54 eV, bottom-gate bottomcontact OFETs (Figure 1b) fabricated by spin-coating showed n-channel characteristics with an electron mobility of the order of 10 − 4 cm 2 V − 1 s − 1 .…”
Section: Introductionmentioning
confidence: 99%